285. Evaluation of the ePlex® Blood Culture Identification (BCID) Panels for Gram-positive/Gram-negative bacteria and yeasts. (31st December 2020) - Chapin, Kimberle; Tansarli, Giannoula
Abstract: Background: Multiple methods used for blood culture identification create inconsistent to reporting of critical results. Study aim was to evaluate performance characteristics of the ePlex BCID panels compared to current standard of care (SOC) methods used in our lab. Methods: Identification sensitivity and specificity were assessed across all targets detected by the ePlex as well as time to final identification (from time of bottle positive Gram stain) between ePlex and SOC testing. SOC included Xpert MRSA/SA or latex agglutination for Gram-positive cocci in clusters (GPCC), Vitek MS + Accelerate Pheno for Gram-negative rods (GNRs), serotyping or optochin disk ± Vitek MS for Gram-positive cocci in chains (GPC chains), Vitek MS or Vitek-2 for Gram-positive rods (GPR), and PNA-FISH or Vitek MS for yeasts. Results: 313 unique prospective blood culture specimens were tested with ePlex BCID panels during a 3-month period (January-March 2020). The positive percent agreement was 100% for GNR (n= 98), S. aureus (n= 42), coagulase-negative staphylococci (n= 38), Group A Streptococcus (n= 3), Group B Streptococcus (n= 5), S. pneumoniae (n= 10), GPR (n= 21), and yeasts (n= 20). There was 1 false negative, ( S.mutans ) which should have been detected. The negative percent agreement was 100% across all targets except for 1 false positive Corynebacterium spp. In total, 6.7% of blood cultures had an off-panel organism which ePlex did not detect. The median time to final identification was 3 (2 – 4) hrs. for ePlex and calculated for all other SOC methods. Compared to SOC molecular methods, the ePlex reduced time to identification 0.5 h compared to Xpert MRSA/SA, 6.7 h compared to Accelerate Pheno for GNR (but Accelerate Pheno provides susceptibilities), and 3 h compared to PNA-FISH for yeasts (p< 0.05). ePlex compared to non-molecular techniques (MALDI-TOF), SOC for Streptococcus spp. and Enteroococcus spp., the time to final identification was reduced by 24 – 30 hours (p< 0.05). Workflow chart comparison eplex to SOC Time to results eplex vs SOC Conclusion: The ePlex BCID system provided highly accurate identification results for GP and GN bacteria as well as for yeasts. Our evaluation showed that this system significantly reduced time to final identification compared to SOC testing methods. Disclosures: Kimberle Chapin, MD, genmark (Scientific Research Study Investigator) Giannoula Tansarli, MD, GenMark (Grant/Research Support)